Dynamics of Social Work Approach in Childcare; An Analysis of Integration of Islamic Kafala Theory and Bowlby’s Attachment Theory and Application Thereof in Childcare in Saudi Arabia - Hani, Sharif (Advances in Humanities and Contemporary Studies, 2024)
This paper explores the dynamic integration of Islamic Kafala theory and attachment theory within the context of childcare and welfare in Saudi Arabia. Despite the growing recognition of diverse cultural and theoretical frameworks in social work practice, there is very limited research on how specific theories are integrated and applied in childcare, particularly within Islamic contexts. This study aims to fill this gap by analyzing the application of these theories in enhancing child welfare and social work practices in Saudi Arabia. Utilizing a mixed-methods approach, the research draws on qualitative data from surveys of child welfare professionals and families engaged in the Kafala system, supplemented by case study analyses in various Muslim countries. The findings reveal that the integration of Islamic Kafala theory and attachment theory offers a culturally sensitive and effective framework for improving childcare practices, promoting the emotional and psychological well-being of children in care. The study highlights practical implications for social workers, suggesting strategies for the successful incorporation of these integrated theories into child welfare practices in Saudi Arabia. It also identifies challenges and limitations within the current system, offering recommendations for policymakers to enhance child welfare services. This research contributes to the theoretical and practical knowledge of childcare and welfare, advocating for a more nuanced and culturally informed approach to social work in Saudi Arabia.